Does the market Reward Corporate Environmentalism? Evidence from Indian IT Firms - Dua, Pritika; Nainwal, Neha (Indian Journal of Finance, 2024)
Purpose : The information technology (IT) sector has been a prominent player in the Indian growth story by accelerating economic growth and advancing standards of living. The sector has reaped rich dividends during the pandemic, with the world transforming to digitalization at a frenzied pace. We cannot overlook the environmental effects of the IT sector, such as e-waste and excessive energy use, even in light of the general recognition of its contributions. Investigating how environmental management practices adoption impacts Indian IT companiesâ€™ market valuation is the goal of this study. Methodology : The impact of corporate environmentalism on firm performance is studied using three market valuation-based measures, namely Tobinâ€™s q, market-to-book value ratio, and excess valuation-to-sales ratio. Corporate environmentalism is measured using a count of environmental management practices (EMPs) along with firm-specific variables like age, advertising expenditure, research and development expenditure, firm size, sales growth, leverage, asset age, and multinational status. We built a unique dataset of 89 listed IT firms over 12 years, from 2008â€“2009 to 2021â€“2022. This study used both static and dynamic panel regression models as econometric tools to investigate how the adoption of EMP affects firm valuation. Findings : The empirical findings demonstrated that two years after the deployment of EMPs, environmentally proactive enterprises saw increases in valuation, demonstrating that the market rewarded such firms. Additionally, we discovered that the firmâ€™s market valuation was significantly impacted by the size of the company and its advertising budget. Practical Implications : The study has implications for management, regulators, and policymakers to promote environmental management as we find fresh evidence that â€œit pays to be green.â€ The IT industry has a crucial position within our industrial ecosystem and possesses the potential to facilitate the integration of sustainable practices with sustainability-focused goods, bridging the gap between local and global contexts as well as connecting the present with the future. Originality : This study focused on the IT industry in a developing country context by building a panel dataset of 89 Indian companies over a 12-year period. Unlike prior research, we built a comprehensive measure of environmental management and addressed endogeneity using static and dynamic panel regression.